Pengaruh Lingkungan Kerja Non Fisik dan Motivasi terhadap Kinerja Karyawan pada PT. Swakarsa Wira Mandiri Gunungsindur Bogor - Abidin, Ali Zaenal; Sopandi, Andi (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study investigates the impact of the non-physical work environment and employee motivation on performance, both individually and collectively, at PT Swakarsa Wira Mandiri in Gunungsindur, Bogor. The background of this research lies in the increasing recognition that employee performance is not solely influenced by physical factors, but also by psychological and motivational elements within the workplace. As companies strive to improve productivity and efficiency, understanding these intangible influences becomes essential for effective human resource management. The research employs a quantitative approach, involving 98 respondents. Data analysis techniques used include instrument testing, validity and reliability tests, normality test, multicollinearity test, heteroscedasticity test, simple and multiple linear regression analyses, correlation coefficient analysis, coefficient of determination, as well as hypothesis testing using t-tests and f-tests. The results indicate that both the non-physical work environment and motivation significantly influence employee performance, both partially and simultaneously. While other external factors may also contribute, these two variables independently show a positive and significant effect on performance. These findings emphasize the importance of psychological and motivational factors in enhancing employee productivity. From a practical standpoint, improving the work environment and strengthening employee motivation can be strategic tools in effective human resource management.